A case report of adult congenital intestinal malrotation - Gao, Yu; Song, Xiaobiao; Song, Qiang (Frontiers in Gastroenterology, 2025)
Congenital intestinal malrotation is a rare congenital digestive tract anomaly, primarily due to the failure of the intestines to rotate and fix properly within the peritoneal cavity during fetal development. This abnormality can lead to severe complications such as intestinal volvulus, intestinal obstruction, and even intestinal necrosis. Although the condition is more commonly seen in neonates, cases in adults have also been reported, often with delayed diagnosis due to atypical symptoms. In this article, we will discuss the diagnosis and treatment of congenital intestinal malrotation in adults.